Unraveling gut microbiota in Parkinson's disease and atypical parkinsonism - Barichella, Michela; Severgnini, Marco; Cilia, Roberto; Cassani, Erica; Bolliri, Carlotta; Caronni, Serena; Ferri, Valentina; Cancello, Raffaella; Ceccarani, Camilla; Faierman, Samanta; Pinelli, Giovanna; Bellis, Gianluca; et al. (Movement disorders, 2019)
ABSTRACT Background Although several studies have suggested that abnormalities in gut microbiota may play a critical role in the pathogenesis of PD, data are still extremely heterogeneous. Methods 16S gene ribosomal RNA sequencing was performed on fecal samples of 350 individuals, subdivided into idiopathic PD (n = 193, of whom 39 were drug naïve) stratified by disease duration, PSP (n = 22), MSA (n = 22), and healthy controls (HC; n = 113). Several confounders were taken into account, including dietary habits. Results Despite the fact that unadjusted comparison of PD and HC showed several differences in relative taxa abundances, the significant results were greatly reduced after adjusting for confounders. Although most of these differences were associated with disease duration, lower abundance in Lachnospiraceae was the only difference between de novo PD and HC (remaining lower across almost all PD duration strata). Decreased Lachnospiraceae and increased Lactobacillaceae and Christensenellaceae were associated with a worse clinical profile, including higher frequencies of cognitive impairment, gait disturbances, and postural instability. When compared with HC, MSA and PSP patients shared the changes in PD, with a few exceptions: in MSA, Lachnospiraceae were not lower, and Prevotellaceae were reduced; in PSP, Lactobacillaceae were similar, and Streptococcaceae were reduced. Conclusions Gut microbiota may be an environmental modulator of the pathogenesis of PD and contribute to the interindividual variability of clinical features. Data are influenced by PD duration and several confounders that need to be taken into account in future studies. Prospective studies in de novo PD patients are needed to elucidate the net effect of dysbiosis on the progression of the disease. © 2018 International Parkinson and Movement Disorder Society